Breaking with the Past: The Renegotiation of Emilia Pardo Bazán’s Legacy and Gonzalo Suárez’s Los pazos de Ulloa - Miller, Gabrielle (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
This essay argues that Gonzalo Suárez’s Los pazos de Ulloa (RTVE 1985) emerges against Francoist narratives that presented Emilia Pardo Bazán and her works in a rather positive (if distorted) light. Through close readings of the gothic and anticlerical passages present in the film, I show how Suárez’s miniseries constructs a new legacy for Pardo Bazán, one that breaks with her favorable reputation during the dictatorship, establishes her relevance in Spain’s secular, newly democratic state, and justifies her privileged place in Spain’s post-Franco canon.